KCNQ1 Potassium Channel Expressed in Human Sperm Is Involved in Sperm Motility, Acrosome Reaction, Protein Tyrosine Phosphorylation, and Ion Homeostasis During Capacitation - Gao, Tian; Li, Kun; Liang, Fei; Yu, Jianmin; Liu, Ajuan; Ni, Ya; Sun, Peibei (Frontiers in Physiology, 2021)
Potassium channels are involved in membrane hyperpolarization and ion homeostasis regulation during human sperm capacitation. However, the types of potassium channels in human sperm remain controversial. The voltage-gated ion channel KCNQ1 is ubiquitously expressed and regulates key physiological processes in the human body. In the present study, we investigated whether KCNQ1 is expressed in human sperm and what role it might have in sperm function. The expression and localization of KCNQ1 in human sperm were evaluated using western blotting and indirect immunofluorescence. During capacitation incubation, human sperm were treated with KCNQ1 specific inhibitor chromanol 293B. Sperm motility was analyzed using a computer-assisted sperm analyzer. The acrosome reaction was studied using fluorescein isothiocyanate-conjugated Pisum sativum agglutinin staining. Protein tyrosine phosphorylation levels and localization after capacitation were determined using western blotting and immunofluorescence. Intracellular K+, Ca2+, Cl-, pH, and membrane potential were analyzed using fluorescent probes. The results demonstrate that KCNQ1 is expressed and localized in the head and tail regions of human sperm. KCNQ1 inhibition reduced sperm motility, acrosome reaction rates, and protein tyrosine phosphorylation, but had no effect on hyperactivation. KCNQ1 inhibition also increased intracellular K+, membrane potential, and intracellular Cl-, while decreasing intracellular Ca2+ and pH. In conclusion, the KCNQ1 channel plays a crucial role during human sperm capacitation.